Big data and climate insurance: reducing risk and maximising revenues : dossier; A Pathway towards agricultural adaptation and resilience;Bundling information and financial services; Innovative insurance for minimising climate risk (2017)
Looks at how accessible agricultural data is facilitating the scaling out of index-based insurance schemes and helping farmers build resilience and adapt to climate change.
Keywords: INSURANCE